Heat and mass transfer coefficients and modeling of infrared drying of banana slices - Baptestini,Fernanda Machado (2017)
ABSTRACT Banana is one of the most consumed fruits in the world, having a large part of its production performed in tropical countries. This product possesses a wide range of vitamins and minerals, being an important component of the alimentation worldwide. However, the shelf life of bananas is short, thus requiring procedures to prevent the quality loss and increase the shelf life. One of these procedures widely used is drying. This work aimed to study the infrared drying process of banana slices (cv. Prata) and determine the heat and mass transfer coefficients of this process. In addition, effective diffusion coefficient and relationship between ripening stages of banana and drying were obtained. Banana slices at four different ripening stages were dried using a dryer with infrared heating source with four different temperatures (65, 75, 85, and 95 ºC). Midilli model was the one that best represented infrared drying of banana slices. Heat and mass transfer coefficients varied, respectively, between 46.84 and 70.54 W m-2 K-1 and 0.040 to 0.0632 m s-1 for temperature range, at the different ripening stages. Effective diffusion coefficient ranged from 1.96 to 3.59 × 10-15 m² s-1. Activation energy encountered were 16.392, 29.531, 23.194, and 25.206 kJ mol-1 for 2nd, 3rd, 5th, and 7th ripening stages, respectively. Ripening stages did not affect the infrared drying of bananas.